Стан та перспективи розвитку зовнішньоекономічної діяльності України - Фольваркова, Вікторія Анатоліївна; Folvarkova, Viktoriya Anatoliyivna (Ірпінь, 2023)
Дослідження базується на визначенні стану та перспектив розвитку зовнішньоекономічної діяльності України. 1) досліджено теоретичні основи здійснення зовнішньекономічної діяльності; 2) визначено принципи ЗЕД, суб’єкти та об’єкти; 3) проаналізовано міжнародну торгівлю товарами та послугами в Україні; 4) досліджено стан інвестиційної діяльності в Україні; 5) узагальнено та охарактеризовано проблеми та перспективи розвитку ЗЕД в Україні.

The study is based on determining the state and prospects for the development of Ukraine's foreign economic activity. 1) the theoretical foundations of foreign economic activity were investigated; 2) the principles, subjects and objects of the FEE are determined; 3) analyzed international trade in goods and services in Ukraine; 4) the state of investment activity in Ukraine was investigated; 5) summarized and characterized the problems and prospects of the development of economic development in Ukraine.
The state and prospects for the development of Ukraine's foreign economic activity
Keywords: ЗЕД; СОТ; ПВЗВТ; ООН; ЄС; ПІІ; FTA; WTO; FTAA; UN; EU; FDI